Analyzing the Impact of Student’s Reading Habits on Academic Performance - Imran Ali; M. Hasnain Raza; Mashad Ali Raza; Nausheen Munawar (International Journal of Scientific Multidisciplinary Research, 2023)
The primary objective of this research was to investigate the reading habits of students and their impact on their academic achievements. The study was conducted within the confines of District Dera Ghazi Khan, specifically focusing on high and higher secondary schools. Employing a qualitative approach, data was collected and analyzed. The results were derived from interviews conducted with six students, serving as a basis for the findings. The research revealed that the majority of the participants recognized the significance of reading, engaging in both scientific literature and fictional works such as stories and novels. Notably, only one student admitted to reading solely with the intention of passing examinations. These outcomes firmly establish the substantial influence of reading habits on academic performance, illustrating a clear correlation between the two. In light of these findings, it is recommended that teachers encourage students to utilize the library for reading purposes and assign additional reading material to foster a stronger reading habit among students